Non-violence approach: the challenge in Philippine broadcasting / Clarita Valdez-Ramos - Clarita, Valdez-Ramos (Centre for Media and Information Warfare Studies, 2008)
The following research is a discussion of the problem that go with freedom in Philippine media and the non-violence approach solution that goes with it. The Philippine society being vulnerable to the deceptions of media's compromised coverage of conflicts, elections and its related gimmicks have now gone used to the traditional way of reportage. The research begins by focusing on the free press and the tribulations that go with such freedom. Continuations are the battle over television ratings that result to compromised coverage of news and the war in Mindanao, southern part of the country and how the media cover it. This paper aims to present the scenario in newsgathering and identify the reasons why some news correspondents sensationalize in news reporting. In addition, this paper aims to provide possible solution to address some problems besetting broadcast journalism in the Philippine setting.